Comparison Between Hesperidin, Coumarin, and Deferoxamine Iron Chelation and Antioxidant Activity Against Excessive Iron in the Iron Overloaded Mice - Aalikhani, Mahdi; Safdari, Yagoub; Jahanshahi, Mehrdad; Alikhani, Mehrdad; Khalili, Masoumeh (Frontiers in Neuroscience, 2022)
Objective. Iron accumulation in the brain leads to the development of Alzheimer's and Parkinson's diseases. Nowadays, iron chelation therapy is the best way to decrease the side effects of iron and amyloid plaques accumulation. Iron chelators are commonly used for the treatment of Alzheimer's disease. Previous studies have shown that natural products such as phenol and flavonoid compounds could chelate heavy metals. In the current study, we examined the iron chelation activity of hesperidin and coumarin on the brain tissue of iron-overloaded mice. Methods. 48 NMRI male mice were divided into eight groups (n=6). Six groups were treated with iron dextran (100 mg/kg/day) four times a week for six weeks. After stopping the injections for a month, five groups of iron-overloaded mice were treated with hesperidin, coumarin, and desferal four times a week subsequent for four subsequent weeks. Finally, the mice were anesthetized, and blood samples were collected from the ventricle of the heart for subsequent examination. The brain tissues were isolated and fixed in the 4% paraformaldehyde solution for Perl's staining. Results. The results show that hesperidin and coumarin could strongly chelate excessive iron from the serum and deposit iron from the brain tissue compared to desferal group. Catalase and super oxidase activity were decreased in the iron-overloaded group, but in the treated group by hesperidin and coumarin, the enzyme's activity was increased significantly. Conclusion. Hesperidin and coumarin, as natural products, are powerful options to chelate iron ions and increase the activity of antioxidant enzymes.